Lateral Nasal Wall Lobular Capillary Hemangioma - A Rare Case Report - Niveda Ramachandran; Parvathi A; Manoj Kumar (Dr. Annil Mahajan, 2023)
Lobular capillary hemangioma is a benign rapidly growing lesion, rare to present as mass filling nasal cavity and paranasal sinuses. They are usually vascular malformation that can occur over face. The involvement of nose and paranasal sinus is rare. It has a property to grow rapidly in a short time and recurrence is also seen. Here we discuss a large lobular capillary hemangioma of the left lateral wall of nasal cavity presenting with recurrent epistaxis.